Conducting management covert investigative (search) actions when investigating thefts committed under martial law - Oliynychuk, Roman; Kanyuka, Valerii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The characteristic features of conducting management secret investigative (research) actions during the investigation of thefts committed during martial law are considered. The views of scientists on the categories related to the specifics of the use and conducting management covert investigative (research) actions in the investigation of thefts committed under martial law were analyzed. The importance of proper planning and conducting management covert investigative (research) actions of law enforcement officials for the successful disclosure of thefts committed during martial law is substantiated. The specifics conducting management individual secret investigative (research) actions during the investigation of thefts committed under martial law were identified and corresponding author's conclusions were drawn. Theft is one of the main property crimes, which has always been a significant part of all criminal statistics in Ukraine.In practice, there are rare cases when offenders do not take their theft seriously, mistakenly believing that nothing terrible will happen to them for it. It would seem, as thieves think, what's the matter here – he appropriated someone else's property. This, in their opinion, happens quite often and this offense is quite widespread in our society. However, now, during the war, such things are treated more strictly. Only coordinated cooperation and mutual understanding between investigators and operatives can ultimately lead to a positive result in terms of quick and high-quality investigation of thefts, as well as professional conduct of pre-trial investigation to achieve its goal and fulfil the tasks of criminal proceedings. Of course, limiting yourself to the use of formal forms and methods in the process of pre-trial investigation, it is not possible to maximally ensure a fast, high-quality and effective investigation of thefts, especially those committed under martial law.